Performance, gut morphology, and meat characteristics of broilers housed at a high-density pen and provided with fermented Averrhoa bilimbi fruit filtrate - Sugiharto, Sugiharto; Yudiarti, Turrini; Widiastut, Endang (Journal of Advanced Veterinary and Animal Research, 2022)
Objective: This study assessed the impact of fermented Averrhoa bilimbi fruit filtrate (FF) on growth, gut morphology, and meat traits of high-stocked broilers. Materials and Methods: A 2 × 2 factorial trial with stocking densities (9 or 18 birds/m2) and drinking 2% FF or plain water was conducted using 378 14-day-old broiler chicks. On day 35, samples were obtained and analyzed. Results: FF improved feed efficiency and income over the feed cost of high-stocked broilers by about 7.63% and 10%, respectively, compared to high-stocked broilers receiving only water. FF decreased duodenal crypt depth and meat water-holding capacity. Meats from high-stocked broilers receiving FF showed lower cholesterol than other meats. Lower cholesterol/high-density lipoprotein (HDL) and higher HDL/low-density lipoprotein were found in meats from broilers receiving FF. Total unsaturated fatty acid (UFA) was higher in meats of high-stocked broilers receiving FF than others. The UFA/saturated fatty acid was lower in meats of high-stocked broilers receiving plain water. High-stocked broilers given FF had higher meat n-3 polyunsaturated fatty acid (PUFA). FF enhanced meat n-6 PUFA levels. The n-3/n-6 PUFA increased with high density and drinking FF. Conclusion: Drinking FF improved gut morphology and meat qualities of broilers housed in high-density pens. FF may be an excellent alternative to improve the growth and meat qualities of broilers raised in high-density houses. J. Adv. Vet. Anim. Res., 9(3): 536–545, September 2022 http://doi.org/10.5455/javar.2022.i623